Barriers to Resolution in Ideologically Based Negotiations: The Role of Values and Institutions - Wade‐Benzoni, Kimberly A.; Hoffman, Andrew J.; Thompson, Leigh; Moore, Don A.; Gillespie, James J.; Bazerman, Max H. (Academy of Management Review, 2002)
Although traditional behavioral decision theory as applied to negotiation sheds light on some of the barriers encountered in negotiations, it does not fully account for many of the difficulties and failures to reach settlement in ideologically based disputes. In this article we identify a number of factors that differentiate ideologically based negotiations from other types of negotiations and advance a perspective that takes into account the value-laden and institutional contexts in which they occur. We illustrate our ideas by applying them to the organizationally relevant example of environmental disputes.